Surgical complications of hemolytic uremic syndrome: Single center experiences - Hooman Nakysa; Otukesh Hasan; Delshad Salahedin; Farhood Pirooz (Wolters Kluwer Medknow Publications, 2007)
Purpose: To determine the prevalence, outcome and prognostic factors in children with hemolytic uremic syndrome (HUS) who underwent laparotomy. Materials and Methods: The medical records of 104 patients with HUS who presented to our center between 1986 and 2003 were reviewed retrospectively. Data were analyzed using Student′s t test for comparing means, Fisher′s exact test for frequencies and Pearson′s correlation for finding the correlations. Results: 78% of cases presented with vomiting and diarrhea. Seven out of 104 needed surgical exploration. The indications of surgery were acute abdomen, severe abdominal distention and the sign of peritonitis. The findings at laparotomy were intussusceptions, perforation (colon, ileum), gangrene of entire colon, rectosigmoidal tearing, duodenal obstruction and toxic megacolon. Pathological findings were transmural infarction in two cases in which staged surgical management was performed (cecostomy, resection, later anastomosis). Four out of seven patients died because of pulmonary failure, coma and multiple organ failure ( P< 0.05) compared to those who did not need laparotomy. The patients requiring surgery were young (< 3 years), had high leukocyte count (>20000 mm 3 ) and low albumin level (< 3g/dl) ( P< 0.05). Conclusion: Surgical complications of HUS are rare but are assorted with high mortality due to respiratory failure and multiple organ failure. Early decision of laparotomy associated with intensive care, including mechanical ventilation, adequate dialysis and ultrafiltration, are recommended.